Experimental study on the variation rule of water level outside the pit caused by dewatering in the pit and the rule of reinjection outside the pit - Yang, Qingyuan; Chen, Song; Yuan, Ying (Frontiers in Materials, 2023)
Studying the surface settlement caused by foundation pit dewatering has certain practical significance for engineering construction. When the aquifer in the foundation pit is located within a large burial depth range, the impermeable wall does not completely separate the water layer, resulting in the water inside and outside the foundation pit communicating around the bottom of the impermeable wall. Taking the foundation pit project of a subway station in Shenzhen as the background, model experiments were conducted to reveal the changes in water level outside the pit caused by precipitation under different conditions inside the pit. (1) Considering the influence of surrounding seepage, the precipitation curve outside the pit presents a concave and then convex form, which is different from the Dupuit theory precipitation curve. (2) For large foundation pit dewatering in layered soil, the downward trend of the dewatering curve outside the foundation pit decreases with the increase of soil depth. (3) Compared to vertical reinjection in close proximity to dense buildings, inclined reinjection has a smaller impact on the side adjacent to the retaining wall, while it is far away from the retaining wall, with a larger impact range. The full well deep reinjection well with an angle of 20° from the vertical direction has the largest reinjection range and the best reinjection effect. It provides a research basis for reasonable control and prevention of surface settlement and adverse deformation of diaphragm walls in narrow spaces under subsequent surrounding seepage conditions.